REPRESENTATIONS OF BORDERLAND IN MALAYSIAN AND INDONESIAN CINEMAS - Mohd Erman Maharam (Proceeding IICACS, 2019)
This paper focuses on 21st century cinematic representations of frontier living in the Malaysian and Indonesian borderland. These representations raise the question of the power relationship between the progressive ‗centre‘ and the less advanced ‗periphery‘. Many of these Borderlands films deal with the issue of identity and belonging as a question of power relations among filmmakers, the people and the state. And some that transect the political and cultural borders of Southeast Asian cinemas stem from the filmmakers‘ growing recognition of the nationalist processes of cultural delimitation and border reinforcement. This investigation reads Dain Said‘s film, Bunohan (2012, Malaysia) and concentrates on representations of the borderland as a site of encounter between the traditions, the modern nation state system and its citizens in these peripheral areas. This paper draws on a chapter from my doctoral thesis, which looks at cinema as a cultural space through the representation of Malaysia, Indonesia, and Singapore.Keywords: Borders, Southeast Asian Borderlands, Malaysian Cinema, Indonesian Cinema